The Bloomsbury handbook to Edwidge Danticat - Braziel, Jana Evans; Clitandre, Nadège T. (Bloomsbury Academic, 2021)
"Edwidge Danticat's prolific body of work has established her as one of the most important voices in 21st century literary culture. Across such novels as Farming the Bones and Krik? Krak!, essays, journalism and writing for children, the Haitian American writer has tackled such important contemporary themes as racism, anti-immigrant politics, sexual violence and imperialism. With chapters written by leading and emerging international scholars this is the most up-to-date and in-depth reference guide to 21st century scholarship on Edwidge Danticat's work. The Bloomsbury Handbook to Edwidge Danticat covers such topics as: The full range of Danticat's writing: from her novels and short stories to essays, life writing and writing for children and young adults; Major interdisciplinary scholarly perspectives: literary studies, politics, feminist and gender studies, race, and ecocriticism; Danticat's literary sources: from Zora Neale Hurston and Audre Lorde to Paule Marshall; Key contexts: Caribbean histories and cultures, experiences of imperialism, migration and diaspora. The book also includes a comprehensive bibliography of Danticat's work and key works of secondary criticism, as well as a new reflective piece by Danticat herself"--
Includes bibliographical references and index
Keywords: Danticat, Edwidge -- 1969- -- Criticism and interpretation; Aufsatzsammlung; Danticat, Edwidge